THE EPISTEMOLOGY OF CLASSICAL ARABIC GRAMMAR: FROM BASHRAH–KUFAH PARADIGM SHIFTS TO CONTEMPORARY LINGUISTICS - Siti Aminah; Siti Arfah; Siti Sumaiah; Husnatul Hamidiyyah Siregar (Universitas Islam Negeri Palopo, 2026)
Epistemological studies of classical Arabic grammar have so far tended to focus on historical descriptions and methodological comparisons between the Basra and Kufa schools, without interpreting their dialectic as a shift in the scientific paradigm that impacts contemporary Arabic linguistics; consequently, the relationship between classical heritage and modern challenges (including pedagogical needs and developments in language technology) has not yet been systematically formulated. This study aims to analyse the epistemological paradigm shift in grammar from the Basra School to the Kufa School and to formulate its implications for the development of contemporary Arabic linguistics. The research employs a qualitative approach utilising a literature review and a historical-philosophical analytical design. The research subjects consist of primary classical nahwu texts, specifically representative works of the Basra and Kufa schools, which are analysed through documentation techniques, conceptual comparison, and diachronic paradigm reconstruction. The research findings indicate that Basra represents a systematic rational-prescriptive paradigm based on qiyas and ta‘lil, whilst Kufa presents an empirical-descriptive paradigm that is more accommodating of linguistic variation and auditory data. The dialectic between the two gave rise to an epistemological crisis that culminated in a methodological synthesis in subsequent developments. The integration of the Bashrah school’s systemic rationality and the Kufah school’s empirical flexibility is theoretically relevant for the reconstruction of the epistemology of nahwu and has practical implications for the development of Arabic language pedagogy and corpus-based linguistic models in the digital age.